The Factors Affecting Financial Effectiveness of Managerial Accounting Information of Small and Medium Enterprises of Para Rubber Industry in Thailand - Pumkaew, Sukrita; Phadoongsitthi, Monvika; Saraphat, Somboon; Sincharoonsak, Titaporn; Chuaychoo, Montree; Penvutikul, Pravas (Asian Administration and Management Review, 2019)
The purpose of this research was to study, develop, and investigate the concordance of the factor models affecting the financial effectiveness of managerial accounting information and empirical evidence. The mailing questionnaires method was used for collecting data between March and August 2017. The response rate was 388 questionnaires (50.72%). The analytical technique was the Structural Equation Model (SEM). The research result revealed that the Model was in accordance with the empirical evidence considered by the value of X2 = 363.10, df = 236, X2/df = 1.54, P = 0.00, RMSEA= 0.037, GFI = 0.93, AGFI = 0.91, CFI = 0.98, RMR = 0.02, and SRMR = 0.024. Moreover, the financial effectiveness was directly affected by the Perceived Environmental Uncertainty on Accounting, Managerial Accounting Information, and Job-Relevant Information. Furthermore, the financial effectiveness was indirectly affected by Ethics of Management Accountants, Accountant’s Budget Participation, Perceived Environmental Uncertainty of Accounting, Job-Relevant Information, Accountant’s Internal Confidence, and Accountant’s Participation in Decision Making through Managerial Accounting Information